"Fixing" the nuclear waste problem? The new political economy of spent fuel management in the United States. (September 2022) - Bell, Marissa Z.; Macfarlane, Allison
Abstract: With continued reliance on nuclear energy in the United States, we are increasingly having to contend with the problem of nuclear waste. Growing quantities of spent nuclear fuel, the lack of permanent storage, and an increasing number of decommissioned nuclear reactors are some of the techno-economic and political realities that have thrust US nuclear waste management into a liminal space of uncertainty. Using a qualitative approach combining policy analysis and case studies, we examine this liminality and the consequent emergence of a new political economy of spent fuel management. Our findings indicate a series of regulatory, organizational and spatial 'fixes' have recently emerged to capitalize on the liminality of nuclear waste management in the US. These fixes include the US Nuclear Regulatory Commission's Continued Storage Rule, the proposal of private consolidated interim storage facilities, and the reconfiguration of nuclear waste management corporations into vertically integrated nuclear waste assemblages with private equity involvement. Such developments are potentially problematic in that they are inherently contradictory, temporary, and quick 'fixes' that do not solve the underlying societal issues, such as distrust in science and lack of democratic governance and energy justice in decision-making, and in many cases they delay permanent solutions. This work contributes to the fields of economic geography, science and technology studies, and nuclear policy studies, by analyzing novel corporate arrangements and developments in the management of spent nuclear fuel in the US. The findings suggest a need to carefully assess policy solutions across contexts, from nuclear waste management to other rapidly evolving energy sectors.